2020
DOI: 10.1021/acsami.0c07540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Bilayer Period of Atomic Layer Deposition on the Growth Behavior and Electrical Properties of the Amorphous In–Zn–O Film

Abstract: This study reports on the effect of a bilayer period on the growth behavior, microstructure evolution, and electrical properties of atomic layer deposition (ALD) deposited In–Zn–O (IZO) films, fixing the ALD cycle ratio of In–O/Zn–O as 9:1. Here, the bilayer period is defined as the total number of ALD cycles in one supercycle of In–O and Zn–O by alternately stacking Zn–O and In–O layers at a temperature of 220 °C. IZO films with a bilayer period from 10 to 40 cycles, namely, IZO­[In–O/Zn–O = 9:1] to IZO[36:4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Lee at al. have shown that ALD IZO using trimethylindium (TMIn), diethylzinc (DEZ) and H 2 O grown at 220 °C is amorphous for In 2 O 3 :ZnO cycle ratios of 9:1 (with Zn and In cycle schedule between our 17 and 20% IZTO film, if the Sn cycle was omitted) and 36:4 (same ratio but different schedule) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee at al. have shown that ALD IZO using trimethylindium (TMIn), diethylzinc (DEZ) and H 2 O grown at 220 °C is amorphous for In 2 O 3 :ZnO cycle ratios of 9:1 (with Zn and In cycle schedule between our 17 and 20% IZTO film, if the Sn cycle was omitted) and 36:4 (same ratio but different schedule) …”
Section: Resultsmentioning
confidence: 99%
“…Full XPS high-resolution survey scans, peak deconvolutions for In 3d, Zn 2p, Sn 3d, and O 1s, and depth profiles from 12 to 33% are shown in the Supporting Information (Figures S1−3 (same ratio but different schedule). 27 Several groups have deposited IZO using magnetron sputtering with In 2 O 3 −ZnO targets (10:90 wt %) at room temperature and at 50 °C resulting in amorphous films as deposited which required heating up to 500 °C to crystallize the IZO films. 28,29 Leenheer et al found that sputter deposited IZO was amorphous from 60 to 84 at% In and could suppress crystallinity up to 600 °C.…”
Section: Ald Of Indium Zinc Tin Oxide At 150 °Cmentioning
confidence: 99%
“…IZO thin films with varying compositions have been deposited by various deposition technologies, such as sputtering [13,16,17,19], pulsed laser deposition [20], thermal evaporation [21], atomic layer deposition [22] and wet-solution process [23].…”
Section: Introductionmentioning
confidence: 99%